Psychological Variables as Correlate of Special Olympic Sports Participation among Persons with Intellectual Disability in Lagos State, Nigeria - Ogabor, Joseph Odey; Apie, Martina Ayibeya; Mohammed, Sanusi; Osaji, Nsagha Nkang; Ahueansebhor, Emmanuel; Odok, Edmond Asu; Adie, Emmanuel Benimpuye; Odok, Anthony Obi; Ntino, Martina Ongbonya; Adie, Boniface Undigweundeye; Okri, John Arikpo; Ukpata, Christiana Ofie; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Introduction: The enthusiasm to participate in Special Olympic sports activities by persons with Intellectual Disability (ID) in Lagos, Nigeria, has been reduced. This research work, therefore, focused on psychological factors and Special Olympic sports participation among persons with mild Intellectual Disability (ID) in Lagos state, Nigeria. Method: Three research hypotheses were formulated to guide the study. A descriptive survey design was adopted; The study participants included 290 parents of persons with mild ID in Lagos state, Nigeria. Purposive and census sampling techniques were used to select the sample. A self-designed research instrument titled Psychological Factors and Sport Participation among Persons with Mild Intellectual Disability Questionnaire (PFSPPMIDQ) was used for data collection in this study. Simple linear regression was used as a tool for data analysis. Result: It was discovered that motivation, anxiety, and stress significantly influence sports participation among persons with mild ID in Lagos state, Nigeria. Conclusion: The study highlights the substantial effect of psychological factors like motivation, anxiety, and stress on Special Olympic sports participation in persons with mild intellectual disabilities in Nigeria. The findings stress the need for focused interventions to enhance motivation and alleviate anxiety and stress to improve participation levels. Special Olympics organizers and sports managers should implement strategies to create a more supportive and encouraging environment, ensuring increased engagement and participants’ overall well-being.